PENGUJIAN KEKASARAN MOLDING BERBASIS ADDITIVE MANUFACTURING MENGGUNAKAN 3D PRINTING MATERIAL ACRYLONITRILE BUTADIENE STYRYNE - Putri, Fenoria; Pratama, Mohammad fauzan; Anwar Sani, Almadora (MACHINERY Jurnal Teknologi Terapan, 2023)
Technological developments move very quickly. Machines are one of the technologies that were created, from existing machines being innovated according to the needs of the times, one of which is 3D Printing. This machine has a special sophistication, which is capable of printing in the form of a prototype whose form is with a drawing on the design in a CAD/CAM application. using Acrylonitrile Butadiene Styrene material. The reason for this test is because the cost of mold production is cheaper than using a molding machine that is commonly used in general, the level of precision is higher than making molding using conventional machines. The method of analysis used the experimental method to determine the effect of treatment on other factors under controlled conditions. Where the resulting mold is tested for surface roughness. From the test results, the data used will be obtained in the form of statistical data analysis, which is carried out using the Analysis of Variance (ANOVA). The analysis that has been applied, concluded that the layer height: low, standard, high has an effect on the roughness of the printed molding, and it can be proven by Fcount 13.026 > Ftable 2.56. with a significant 0.014 < 0.05. The lowest roughness results are printed using a layer height: 0.16 mm/s (high quality).